PENYANDIAN TEXTS CHAT VIA INTERNET DENGAN ALGORITMA VIGENERE CIPHER BERBASIS ANDROID - Aulia, Rachmat; Sembiring, Arnes; Zakir, Ahmad; Siregar, Budi Arisa Utomo (Jurnal Sistem Informasi Kaputama (JSIK), 2019)
One feature of a smartphone device that is still often used is the exchange of messages such as text chat. This exchange of information generally knows no distance, can be far or close. This requires security of the confidentiality of information sent from the source to the target. One way to get the security of communication is by applying cryptographic techniques so that the message sent to the target can be secured. The cryptographic technique used in this study is Vigenere Cipher. The Vigenere Cipher algorithm is used to encode text conversations so that messages sent via the internet can be maintained as well as with confidentiality. The purpose of this study is to build a text conversation cryptographic application that can run on Android-based smartphone devices. The technique can encrypt text conversations into secret messages which then the results (messages) are sent using a message sending application such as SMS (Short Message Service), Whatsapp and Line. Then when the message arrives at the destination, the description is done automatically so that the original message can be read.